Pesantren sebagai Pusat Peradaban Muslim : Pengalaman Indonesia untuk Asia Tenggara - Kamaruzzaman Bustamam Ahmad (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2010)
This paper aims to examine the contribution of pesantren for Islamic civilization. it argues that pesantren has contributed to the history of Islam in Southeast Asia. in this study, the author surveys the socio-historical of the development of pesantren. this study discuses the philosophical aspect Islamic education in pesantren. this can be understood by examining the concept of self in process reproduction of ulama. the main point of this article is to seek the foundation for argument that the experience of Muslim in pesantren in Indonesia can be a model for Southeast Asia countries.